(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Stunting remains a major health problem in Indonesia, particularly among vulnerable groups such as pregnant women and toddlers. This condition reflects chronic malnutrition influenced by various social, economic, cultural, and environmental factors. Preventive measures need to be implemented during pregnancy, particularly during the first 1,000 days of life (HPK), a crucial phase for a child’s growth and development. In this context, Posyandu Melati III plays a crucial role in supporting stunting prevention through nutritional status assessments for pregnant women and toddlers. The activity was carried out on Monday, November 17, 2025 at 10:00 WIB, with 32 participants consisting of pregnant women and mothers with toddlers. The series of activities included anthropometric measurements on toddlers and LILA on pregnant women, accompanied by recording the results in the KIA book and growth charts, as well as counseling on balanced nutrition. The results of this community service program enable early detection of various nutritional issues such as CED, anemia, and the risk of low birth weight (LBW) in pregnant women, as well as underweight, wasting, and early signs of stunting in toddlers. In addition to screenings, education is provided to increase family understanding of the importance of exclusive breastfeeding, PMT (Food and Nutritional Supplement), and implementing a nutritious daily diet. The findings of this activity demonstrated high levels of community participation and increased knowledge regarding stunting prevention efforts. The data obtained also served as a basis for health workers and cadres to plan more targeted follow-up and interventions. Overall, integrated health post (Posyandu) activities have been shown to contribute to early detection and prevention of stunting, as well as improving maternal and child health through a community-based promotive and preventive approach.